SRATEGI PENGEMBANGAN EKONOMI KREATIF MELALUI KOMUNITAS MUDA MUDI BERSOSIAL (MMB) DESA BOTONA’AI KECAMATAN TUGALA OYO KABUPATEN NIAS UTARA - Waruwu, Vince Putra Jaya (Universitas Nias Raya, 2025)
This research is motivated by experiencing deficiencies in financial and capital aspects, experiencing obstacles or deficiencies in aspects. The purpose of this study is to describe the strategy of creative economy development through the social youth community (MMB) of Botona'ai Village, Tugala Oyo District, North Nias Regency. This type of research is a type of qualitative research with a descriptive approach. The results of the research found are the role of village government in Developing a community-based creative economy, the government's desire to make creative villages, adequate quality of human resources. Advice is It is expected that creative industry players, as those who are directly involved in the development of the creative economy, are expected to develop design innovations and can maximize technology to promote products that have been produced so that marketing can reach a wider area and make Botona'ai Village, Tugala Oyo District, North Nias Regency known by the wider community as a creative village.